Pola Komunikasi Guru Terhadap Siswa Down Syndrome di Sekolah Luar Biasa Negeri Kota Samarinda - Ade Aulia Martha; Silviana Purwanti; Kadek Dristiana Dwivayani (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2022)
Down syndrome experience mental retardation and have IQ scores below the average of normal people so that make teachers who teach in schools experience difficulty in communicate with students who experience down syndrome. Because of that, School teacher Outside Ordinary Samarinda City Country when teach student down syndrome use method communicate and teach differently with other teachers. This article arranged with objective for for analyze pattern teacher communication in process study teach child down syndrome di School Outside Ordinary Samarinda City State. Method writing article this use method studies case. As for the results studies show that the teacher does approach more formerly to students so that they can understand the ability of each student. Teacher teaching student down syndrome using verbal symbols (simple and gradual language) and non-verbal (gestures body, expression face, action, usage object physical). along with intense communication from environment school (teacher) then will give great influence for development students. As for the role of parents student in thing this is very important in guide and motivate her son when study at home.